Self‐Assembly of Microparticles by Supramolecular Homopolymerization of One Component DNA Molecule. Issue 26 (8th February 2019) - Zeng, Jie; Fu, Wenhao; Qi, Zhenping; Zhu, Qiushuang; He, Huawei; Huang, Chengzhi; Zuo, Hua; Mao, Chengde
Abstract: DNA is a superb molecule for self‐assembly of nanostructures. Often many DNA strands are required for the assembly of one DNA nanostructure. For lowering the cost of synthesizing DNA strands and facilitating the assembly process, it is highly desirable to use a minimal number of unique strands for potential technological applications. Herein, a strategy is reported to assemble a series of DNA microparticles (DNAµPs) from one component DNA strand. As a demonstration of the application of the resulting DNAµPs, the design and assembled DNAµPs are modified to carry additional single‐stranded tails on their surfaces. The modified DNAµPs can either capture other nucleic acids or display CpG motifs to stimulate immune responses. Abstract : A minimalist approach is reported here to assemble microscaled DNA particles (DNAµPs) . Each type of DNAµP requires only one type of DNA oligonucleotide, making this approach cost‐effective and experimentally simple. Such DNAµPs have been demonstrated to be able to sequester other single‐stranded DNA molecules or display functional DNA molecules on their surfaces.